THE RELATIONSHIP BETWEEN CORPORATE CODE OF CONDUCT, MORAL REASONING AND ETHICAL DECISION MAKING AMONG TAKAFUL AGENTS IN MALAYSIA - NorAin Binti Mohammad Sopian; Dr Adi Anuar Bin Azmin (International Journal of Accounting, Finance and Business, 2020)
common management task in organization is to act and decide ethically and the focus is fall on the ethical reasoning factors that make up the mind of decision maker. In businesses, ethical issues are the major concern as it gives impact on various parties such as customers, employees, shareholders and society. Takaful industry has evolved in preceding years and the dispersion of Takaful products is growing year by year and it is believed that remarkable growth and performance of Takaful industry is due to the superior ethics and values which support the principle of brotherhood and mutual assistance as a mechanism for risk sharing pooling. This research used 150 respondents from Takaful industry and four Takaful companies were selected based on consumers favourites which is Takaful Malaysia, Takaful Ikhlas, Etiqa Takaful and Zurich Takaful. The parameters from two models namely issuecontingent model of ethical decision making by individual by Thomas M Jones (1991) (moral intensity) and the interactionist model of ethical decision making in organization by Linda Klebe Trevino (1986) (individual attributes) were utilized in this research.